Compartimentalização da resposta imune e sua relação com o perfil de citocinas em diferentes órgãos de cães leishmaniose visceral - Bandarra, Márcio de Barros [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The immune response of dogs with visceral leishmaniasis (VL) may present a varied profile of cytokines, predominantly proinflammatory (resistance) or anti-inflammatory (susceptibility) cytokines, hindering or favoring the multiplication of the protozoan Leishmania infantum chagasi in the host tissues. In these animals there is an imbalance between the profiles of Th1 and Th2 immune response. The evaluation of the immune response of these dogs with different clinical manifestations of VL is crucial for understanding the pathogenesis of the disease. The aim of this study was to evaluate the profile of Th1, Th2 and regulatory cytokines, transcription factors (T-bet and GATA-3) and parasite load in dogs with VL and control, in the liver, spleen and popliteal and prescapular lymph nodes to verify possible differences in compartmentalized immune response. In this study 28 dogs from an endemic area for VL and five dogs from non-endemic area (control) were used. The infected dogs were divided into symptomatic (n = 16) and asymptomatic (n = 12) groups of dogs. The quantification of the gene expression of cytokines (IFN-γ, TGF-β, IL-10, IL-4, IL-12 and MIF) and tissue parasitic load of the transcription factors was done using the technique of quantitative PCR in real time, tissue samples from different organs. The spleen and popliteal and pre-scapular lymph nodes were the organs that showed a higher number of copies of the DNA of Leishmania infantum chagasi. The results of the expression of cytokine genes showed that there was an increased expression of pro-inflammatory (TNF-α, IFN-γ, MIF, IL-12), anti-inflammatory (IL-4) and regulatory cytokines (IL-10 , TGF-β) in groups of infected dogs, with some significant differences from the control group (P <0.05). While the transcription factor T-bet had higher levels in asymptomatic animals. In conclusion GATA-3 was less expressed in the group of infected dogs suggesting that there other mechanisms ...

A resposta imune de cães com Leishmaniose Visceral (LV) pode apresentar um perfil variado de citocinas, com predominância de citocinas pró-inflamatórias (resistência) ou antiinflamatórias (susceptibilidade), dificultando ou favorecendo a multiplicação do protozoário Leishmania infantum chagasi nos tecidos do hospedeiro. Nesses animais existe um desequilíbrio entre os perfis das respostas imunes Th1 e Th2. A avaliação da resposta imunológica destes cães com diferentes manifestações clínicas de LV é de fundamental importância para a compreensão da patogenia da doença. O objetivo geral deste estudo foi avaliar o perfil de citocinas Th1, Th2 e regulatórias, fatores de transcrição (T-bet e GATA-3) e carga parasitária em cães com LV e controle, no fígado, baço e linfonodos poplíteo e pré-escapular, para verificar possíveis diferenças na resposta imune compartimentalizada. Neste estudo foram utilizados 28 cães de área endêmica para a LV e cinco cães de área não endêmica (controle). Os cães infectados foram separados em grupos sintomático (n=16) e assintomático (n=12). A quantificação da expressão dos genes das citocinas (IFN- γ, TGF-β, IL-10, IL-4, IL-12 e MIF), da carga parasitária tecidual e dos fatores de transcrição foi feita por meio da técnica de PCR quantitativo em tempo real, em amostras de tecidos dos diferentes órgãos. O baço e os linfonodos poplíteo e pré-escapular foram os órgãos que apresentaram maior número de cópias do DNA da Leishmania infantum chagasi. Os resultados da expressão dos genes de citocinas mostraram que houve um aumento da expressão de citocinas pró-inflamatórias (TNF-α, IFN-γ, MIF, IL-12), anti-inflamatórias (IL-4) e regulatórias (IL-10, TGF-β) nos grupos de cães infectados, algumas com diferenças significativas do grupo controle (P<0,05). Enquanto o fator de transcrição T-bet teve níveis mais elevados nos animais assintomáticos. Em conclusão ...
Keywords: Cão - Doenças; Leishmaniose visceral; Resposta imune; Leishmania; Citocinas; Cytokines